Tourism and Hospitality internships in Higher Education: A competency-based framework - Quintela, Joana (2023)
Higher education internships have the general goal of providing an active learning experience that supplements classroom learning, helping students transition to the labor market. Thus, internships can provide a valuable practical background to entering the labor market. Through internships, students can develop and apply the skills, theories, and concepts learned in their study programs, as well as gain industry-specific knowledge and competencies, enhancing their employability. Internships are also perceived as critical experiences influencing students’ decisions to join the tourism and hospitality workforce. First-hand experiences can give students a more robust and realistic view of the industry, playing a decisive role in shaping their future behavior. This research aims to contribute to a deeper understanding of the on-the-job training experiences of tourism and hospitality management students, modeling a competency-based framework. An exploratory research approach was adopted, combining theoretical and empirical methods: a comprehensive review of the extant literature on relevant skills and competencies for the tourism and hospitality industry and the analysis of undergraduate students’ accounts collected from internship reports that offered insights into the practical experiences of students and the competencies developed herewith. This study proposes a conceptual framework that integrates three sets of competencies: (i) cognitive and functional competencies, (ii) personal and social competencies, and (iii) professional competencies. Active learning experiences such as internships are posited as part of a formative continuum that begins with undergraduate education and transfers to the labor market. The proposed framework advances research in higher-level skill development and assists educators and organizational leaders in developing a graduate-level skilled workforce more efficiently by considering the strategic role of internships.